Price Adjustment Costs, Anticipated Inflation, and Output - Kuran, Timur (Quarterly Journal of Economics, 1986)
Journal Article Price Adjustment Costs, Anticipated Inflation, and Output Get access Timur Kuran Timur Kuran University of Southern California Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 101, Issue 2, May 1986, Pages 407–418, https://doi.org/10.2307/1891122 Published: 01 May 1986